Factors Associated With Neck Hematoma After Thyroidectomy: A Retrospective Analysis Using a Japanese Inpatient Database. Issue 7 (February 2016) - Suzuki, Sayaka; Yasunaga, Hideo; Matsui, Hiroki; Fushimi, Kiyohide; Saito, Yuki; Yamasoba, Tatsuya
Abstract : Abstract: To identify risk factors for post-thyroidectomy hematoma requiring airway intervention or surgery ("wound hematoma") and determine post-thyroidectomy time to intervention. Post-thyroidectomy hematoma is rare but potentially lethal. Information on wound hematoma in a nationwide clinical setting is scarce. Using the Japanese Diagnosis Procedure Combination database, we extracted data from records of patients undergoing thyroidectomy from July 2010 to March 2014. Patients with clinical stage IV cancer or those with bilateral neck dissection were excluded because they could have undergone planned tracheotomy on the day of thyroidectomy. We assessed the association between background characteristics and wound hematoma ≤2 days post-thyroidectomy, using multivariable logistic regression analysis. Among 51, 968 patients from 880 hospitals, wound hematoma occurred in 920 (1.8%) ≤2 days post-thyroidectomy and in 203 (0.4%) ≥3 days post-thyroidectomy (in-hospital mortality = 0.05%). Factors significantly associated with wound hematoma ≤2 days post-thyroidectomy were male sex (odds ratio [OR] 1.52, 95% confidence interval [CI] 1.30–1.77); higher age (OR 1.01, 95% CI 1.00–1.02); overweight or obese (OR 1.22, 95% CI 1.04–1.44); type of surgery (partial thyroidectomy for benign tumor compared with: total thyroidectomy, benign tumor [OR 1.95, 95% CI 1.45–2.63]; partial thyroidectomy, malignant tumor [OR 1.21, 95% CI 1.00–1.46]; total thyroidectomy, malignant tumor [OR 2.49, 95% CI 1.82–3.49]; and thyroidectomy for Graves disease [OR 3.88, 95% CI 2.59–5.82]); neck dissection (OR, 1.53, 95% CI 1.05–2.23); antithrombotic agents (OR 1.58, 95% CI 1.15–2.17); and blood transfusion (OR 5.33, 95% CI 2.39–11.91). Closer monitoring of airway and neck is recommended for patients with risk factors, and further cautious monitoring beyond 3 days post-thyroidectomy.